THE IMPACT OF RUSSIA’S WAR AGAINST UKRAINE ON THE GLOBAL SPACE SECTOR - Borotkanych, Nataliia (Стратегічна панорама, 2023)
Russia’s war against Ukraine has had a significant impact on both global security in general and the space sector in particular. The article explores the specific uses of satellites, including civilian and dual-purpose, in relation to both combat and national security in broad terms. The purpose of the study is to analyze the impact of the Ukrainian-Russian war on the global space sector. The author argues that although the use of space technologies in military conflicts has historical precedents, the Russian-Ukrainian war has launched processes that have led to fundamental changes in the field of space security. The factors motivating these changes include, firstly, the growing independence of the EU space segment, which has long relied on Russia. Secondly, there is an increase in demand for satellite images, including radar images. Thirdly, the importance of low-orbit Internet for both military and civilian users in combat zones has been growing. The war has also changed the practices of space launches, which need to become even faster and cheaper to quickly replace satellites that have been attacked. This war revealed the weaknesses of space systems and a number of threats, including: the possibility of using satellite data for criminal purposes, the vulnerability of space infrastructure (for example, cyber attacks and signal jamming), as well as the limited range of suppliers of goods and services in the space sector, which makes supply chains unstable and vulnerable. Conflicts on Earth increase the risks of satellite collisions in space. Escalation can occur not only due to the deliberate action of one of the participants in space activities, but also accidentally due to the increase in the number of objects in near-Earth orbit. The author argues that Russia’s full-scale invasion of Ukraine has more than clearly demonstrated the role that space plays in modern warfare. The United States, China and other major players are now carefully studying the experience of combat operations in Ukraine and in the near future we will see the launch of new satellites and the strengthening of existing groups of spacecraft.